Conversational implicature used by 4 main characters in Extra English series = Hàm ý hội thoại bốn nhân vật chính sử dụng trong bộ phim Extra English. M.A Thesis Linguistics: 822020101 - Phạm, Thị Thanh Loan (2019)
This research aims to identify the types of maxims flouting performed by four main characters, to explain the strategies and reasons used by four main characters to flout the maxims. Moreover, the study is undertaken as an attempt to discover the similarities and differences in their habits of flouting maxims